2020
DOI: 10.1002/ejoc.201901841
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Bioreduction of Telluro‐Acetophenones to Optically Active Hydroxy Tellurides

Abstract: Organotellurium compounds exhibit a broad range of useful applications in organic synthesis, materials science and medicinal chemistry fields. Despite their increasing applicability, the synthesis of enantiomerically pure organotellurium compounds remains nowadays scarcely reported in the literature. Herein, the chemical synthesis and biocatalyzed reductions of a set of telluro‐acetophenones using both (R) and (S)‐selective alcohol dehydrogenases (ADHs) is described for the first time, obtaining enantiomerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…This is also why "chemical" regeneration systems represent a viable alternative to enzymatic counterparts. The preferred stoichiometric electron acceptor is molecular oxygen because of the high thermodynamic driving force of O 2 reduction on the one hand and because of the favorable byproducts (H 2 O or H 2 O 2 , which is generally (Bandeira et al, 2020), [h] RsADH (from Rhodococcus sp.) (Rosen et al, 2006).…”
Section: Regeneration Of Reduced Nicotinamide Cofactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also why "chemical" regeneration systems represent a viable alternative to enzymatic counterparts. The preferred stoichiometric electron acceptor is molecular oxygen because of the high thermodynamic driving force of O 2 reduction on the one hand and because of the favorable byproducts (H 2 O or H 2 O 2 , which is generally (Bandeira et al, 2020), [h] RsADH (from Rhodococcus sp.) (Rosen et al, 2006).…”
Section: Regeneration Of Reduced Nicotinamide Cofactorsmentioning
confidence: 99%
“…Ketones comprising one large and one small substituent at the carbonyl group are very common substrates for ADH-catalysed reductions. Especially methyl ketones are popular starting materials and a broad range of aliphatic (Sinha and Keinan, 1997), aromatic (Hamada et al, 2001;Stampfer et al, 2002;Hummel et al, 2003;Gonzalez-Martinez et al, 2019;Bandeira et al, 2020), and conjugated ketones (Schubert et al, 2001;Sgalla et al, 2007;Albarrán-Velo et al, 2020;González-Granda et al, 2021) have been reported. Figure 11 shows a representative selection of chiral alcohols obtained from the reduction of methyl ketones.…”
Section: Adh-catalysed Reduction Reactionsmentioning
confidence: 99%